Evaluation of weather influence on mechanical and viscoelastic properties of polyetherimide/carbon fiber composites - Batista, Natassia L.; Iha, Koshun; Botelho, Edson C. [UNESP] (SAGE Publications, 2013)
In order to investigate how environmental degradation affects the mechanical and thermal performance of polyetherimide/carbon fiber laminates, in this work different weathering were conducted. Additionally, dynamic mechanical analysis, interlaminar shear strength tests and non-destructive inspections were performed on this composite before and after being submitted to hygrothermal, UV radiation and thermal shock weathering. According to our results, hygrothermally aged samples had their glass transition temperature and elastic and storage moduli reduced by plasticization effect. Photooxidation, due to UV radiation exposure, occurred only on the surface of the laminates. Thermal shock induced a reversible stress on the composite's interface region. The results revealed that the mechanical behavior can vary during weather exposure but since this variation is only subtle, this thermoplastic laminate can be considered for high-performance applications, such as aerospace. © The Author(s) 2013.
Keywords: carbon fiber; environmental degradation; Polyetherimide; High performance applications; Inter-laminar shear strengths; Mechanical behavior; Non destructive inspection; Plasticization effects; Radiation Exposure; Thermal Performance; Viscoelastic properties; Carbon fibers; Photooxidation; Polyetherimides; Thermal shock; Ultraviolet radiation; Weathering; Laminates